LIPID PROFILE IN OBESITY - Bhatti, Muhammad Sarwar; Akbri, M. Zamir Ahmad; Shakoor, Muhammad (Journal of Ayub Medical College Abbottabad, 2001)
Background: Obesity is associated with social and medical risks that especially make it a problem. The importance of obesity in the prediction of cardiovascular disease has been the subject of long standing debate. Direct correlation between plasma triglycerides and body weight have been noticed. We report the results of a study in our center. Methods: Fifty adult subjects who were obese (body mass index > 25 Kg/m) and nonsmokers were selected along with thirty non obese nonsmokers as controls. Lipid profile was studied including total lipids, total cholesterol. HDL, LDL, VLDL and chylomicrons. Various ratios like LDL/HDL, VLDL/HDL, TG/HDL and TC/HDL ratios were calculated to find the risk of atherosclerosis and coronary heart disease. Results: All the parameters except serum HDL. level showed significant increase in obese persons while HDL level was significantly decreased.